One-Shot Tagging During Wake and Cueing During Sleep With Spatiotemporal Patterns of Transcranial Electrical Stimulation Can Boost Long-Term Metamemory of Individual Episodes in Humans - Pilly, Praveen K.; Skorheim, Steven W.; Hubbard, Ryan J.; Ketz, Nicholas A.; Roach, Shane M.; Lerner, Itamar; Jones, Aaron P.; Robert, Bradley; Bryant, Natalie B.; Hartholt, Arno; Mullins, Teagan S.; Choe, Jaehoon; et al. (Frontiers in Neuroscience, 2020)
Targeted memory reactivation (TMR) during slow-wave oscillations (SWOs) in sleep has been demonstrated with sensory cues to achieve about 5-12% improvement in post-nap memory performance on simple laboratory tasks. But prior work has not yet addressed the one-shot aspect of episodic memory acquisition, or dealt with the presence of interference from ambient environmental cues in real-world settings. Further, TMR with sensory cues may not be scalable to the multitude of experiences over one’s lifetime. We designed a novel non-invasive non-sensory paradigm that tags one-shot experiences of minute-long naturalistic episodes within immersive virtual reality with unique spatiotemporal amplitude-modulated patterns (STAMPs) of transcranial electrical stimulation. In particular, we demonstrated that these STAMPs can be re-applied as brief pulses during SWOs on two consecutive nights to achieve about 20% improvement in the metamemory of targeted episodes compared to the control episodes. We found that STAMPs can not only facilitate but also impair metamemory for the targeted episodes based on an interaction between pre-sleep metamemory and the number of STAMP applications during sleep. Overnight metamemory improvements were mediated by spectral power increases following the offset of STAMPs in the slow-spindle band (8-12 Hz) for left temporal areas in the scalp electroencephalography (EEG) during sleep. These results prescribe an optimal strategy to leverage STAMPs for boosting metamemory and suggest that real-world episodic memories can be modulated in a targeted manner even with coarser, non-invasive spatiotemporal stimulation.